Recognizing Faith: A Perspective on Black Caribbean Immigrant Women - Dixon, Sandra P.; Arthur, Nancy M. (Canadian Journal of Counselling and Psychotherapy, 2019)
Faith plays important roles in the reconstruction of cultural identities for many immigrants, in particular for Black Caribbean immigrant women (BCIW). By understanding and appreciating the religious and spiritual dimensions of people’s cultural identities, counsellors can enhance their knowledge when addressing salient aspects of faith in approaches to counselling. The discussion is intended to orient and demystify key practices within the Judeo-Christian Protestant tradition (specifically Pentecostal faith), address relevant feminist debates over the social positioning of women in this faith tradition, and highlight counselling implications for the culture-infused counselling model that emphasizes a social justice lens.